Phasic dopamine modifies sensory-driven output of striatal neurons through synaptic plasticity - Wieland, Sebastian; Koehr, Georg (The journal of neuroscience, 2015)
Animals are facing a complex sensory world in which only few stimuli are relevant to guide behavior. Value has to be assigned to relevant stimuli such as odors to select them over concurring information. Phasic dopamine is involved in the value assignment to stimuli in the ventral striatum. The underlying cellular mechanisms are incompletely understood. In striatal projection neurons of the ventral striatum in adult mice, we therefore examined the features and dynamics of phasic dopamine-induced synaptic plasticity and how this plasticity may modify the striatal output. Phasic dopamine is predicted to tag inputs that occur in temporal proximity. Indeed, we observed D1 receptor-dependent synaptic potentiation only when odor-like bursts and optogenetically evoked phasic dopamine release were paired within a time window of <1 s. Compatible with predictions of dynamic value assignment, the synaptic potentiation persisted after the phasic dopamine signal had ceased, but gradually reversed when odor-like bursts continued to be presented. The synaptic plasticity depended on the sensory input rate and was input specific. Importantly, synaptic plasticity amplified the firing response to a given olfactory input as the dendritic integration and the firing threshold remained unchanged during synaptic potentiation. Thus, phasic dopamine-induced synaptic plasticity can change information transfer through dynamic increases of the output of striatal projection neurons to specific sensory inputs. This plasticity may provide a neural substrate for dynamic value assignment in the striatum.
Gesehen am 08.02.2018